PENGEMBANGAN DESA WISATA ADAT KOTO SENTAJO KABUPATEN KUANTAN SINGINGI - Safitri, Tiwi; SD, Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Koto Sentajo Traditional Tourism Village is one of the cultural tourism destinations in Kuantan Singingi Regency which was developed by the Tourism and Culture Office of Kuantan Singingi Regency. This village has the potential for local customs and culture, traditional food, traditional games, the building of the godang house and the old mosque of Raudhatul Jannah which is still authentic. This potential is then packaged and developed into one of the tourist objects in Kuantan Singingi Regency. But this potential has not been supported by good management and development. This can be seen from the condition of supporting facilities for tourism village areas which are still limited, coupled with the lack of public understanding of tourism, so that to market their tourist villages they still depend on related agencies. The purpose of this study is to determine and analyze the development of the traditional tourism village of Koto Sentajo, Kuantan Singingi Regency and to determine the inhibiting factors for the development of the traditional tourism village of Koto Sentajo, Kuantan Singingi Regency. This research uses purposive sampling technique with using a phenomenologhical approach qualitative research type. The collection of data obtained both primary data and secondary data were collected through interviews, observation and documentation then analyzed based on research problems. The results of this study indicate that the development of the traditional tourism village of Koto Sentajo, Kuantan Singingi Regency is still not optimal, this is due to several inhibiting factors, namely the lack of human resource capacity, limited budget or funds, not optimal partnerships and lack of community participation.Keyword : Development, Traditional Tourism Village, Koto Sentajo